2007
DOI: 10.1007/s10096-007-0269-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an enrichment broth-enhanced commercial PCR procedure versus bacteriological culture for separating non-colonized from suspected or colonized MRSA individuals

Abstract: The aim of the study presented here was to evaluate an enrichment broth-enhanced commercial PCR procedure for excluding the presence of meticillin-resistant Staphylococcus aureus (MRSA) in patient samples in less than 36 h. In The Netherlands to date, all MRSA epidemics have been successfully controlled with the Dutch search-and-destroy policy. However, PCR facilitates more rapid screening for MRSA than traditional culture. One commercial PCR option is the hyplex StaphyloResist(R) PCR assay (Biologische Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…NPVs were similar and high for both methods (99.5%); however, the PPV for the Hyplex StaphyloResist was only 31.4% (11). Wagenvoort et al showed that pooling specimens (nose, throat, perineum, wounds/infections) followed by an 18-h enrichment in a nonselective broth could increase the sensitivity (97.6%), and to some extent, the PPV (37.4%) of the Hyplex StaphyloResist, while still retaining a high specificity (83.7%) and NPV (99.7%) (41). A markedly low PPV and a high frequency of false-positive results are observed with the Hyplex StaphyloResist assay because this assay detects two unlinked markers (an S. aureus species-specific gene and mecA), and mixed cultures of MSSA and MRCoNs are likely to give positive results.…”
Section: Molecular Diagnostics For Mrsamentioning
confidence: 99%
“…NPVs were similar and high for both methods (99.5%); however, the PPV for the Hyplex StaphyloResist was only 31.4% (11). Wagenvoort et al showed that pooling specimens (nose, throat, perineum, wounds/infections) followed by an 18-h enrichment in a nonselective broth could increase the sensitivity (97.6%), and to some extent, the PPV (37.4%) of the Hyplex StaphyloResist, while still retaining a high specificity (83.7%) and NPV (99.7%) (41). A markedly low PPV and a high frequency of false-positive results are observed with the Hyplex StaphyloResist assay because this assay detects two unlinked markers (an S. aureus species-specific gene and mecA), and mixed cultures of MSSA and MRCoNs are likely to give positive results.…”
Section: Molecular Diagnostics For Mrsamentioning
confidence: 99%
“…Despite increasing knowledge, more rapid detection techniques, including PCR [6], and interventions with regard to the multi-resistant strains problem and optimal treatment of infection-diseased patients worldwide, the trends in recent years show that the future pertaining to MRSA is not viewed optimistically by various experts in the field.…”
Section: Discussionmentioning
confidence: 99%
“…The reference literature for the individual countries is listed as follows: A: [7], [8], [9], [10], [11], D: [12], [13], [14], [15], [16], [17], [18], [19], DK/FI/SE/NO/IS: [20], [21], [22], [23], [24], [25] [26], ES: [27], [28], [29], [30], [31], [32], [33], [34], [35], FR: [36], [37], [38], [39], [40], HU: [41], [42], [43], IT: [44], [45], [46], [47], [48], [49], JP: [50], [51], [52], [53], [54], [55], [56], [57], [58], NL: [6], [59], [60], [61], [62], [63], [64], [65]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 The sensitivity and specificity of the hyplex StaphyloResist assay in the detection of MRSA have been tested in studies involving the use of nasal swabs and other body-surface swabs, but the assay has not been evaluated as a tool to guide antimicrobial therapy. 12,13 Generally, the assay was found to have reasonably good sensitivity, but its specificity (83.7-90%) was deemed to be on the low end of the range of acceptability; such marginal specificity could result in a substantial rate of false-positive results if the assay were to be put into widespread use.…”
Section: Currently Available Rapid Mrsa Testsmentioning
confidence: 98%